Discourses Underpinning Parenting Training Programmes: Positioning and Power. (3rd May 2013) - Cottam, Susan; Espie, Jonathan
<x xml:space="preserve">Abstract</x> Parenting training programmes (PTPs) aim to improve parenting skills and are widely offered in the UK. Despite evidence of efficacy, this paper hypothesises that PTPs may risk disempowering parents, children and even facilitators by prioritising professional expertise over lay knowledge. A Foucauldian discourse analysis examined six PTP manuals and identified discourses including victimhood, institutional salvation, scientism and collaboration. Power relations favouring government and professionals, and impacting outcomes and parental engagement were suggested to result from some of these discourses. Research into PTP engagement in terms of power relations and acknowledgement by policy‐makers of the impact of discourse was recommended.